Potere e lotta delle mondariso vercellesi ai primi del Novecento - Sacco-Morel, Michela (Italogramma, 2021)
<span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*253.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.956252);" role="presentation">Between the end of the nineteenth century and the beginning of the twentieth century, the <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*273.79px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.916986);" role="presentation">women rice weeders <span dir="ltr" style="left: calc(var(--scale-factor)*176.06px); top: calc(var(--scale-factor)*273.79px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.961916);" role="presentation">gained political visibility and participated in the construction of a new <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*294.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.905572);" role="presentation">emancipatory and egalitarian law. From the<span dir="ltr" style="left: calc(var(--scale-factor)*278.69px); top: calc(var(--scale-factor)*294.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.10285);" role="presentation">ir <span dir="ltr" style="left: calc(var(--scale-factor)*288.77px); top: calc(var(--scale-factor)*294.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.941662);" role="presentation">first claims <span dir="ltr" style="left: calc(var(--scale-factor)*344.95px); top: calc(var(--scale-factor)*294.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.891853);" role="presentation">that were <span dir="ltr" style="left: calc(var(--scale-factor)*391.63px); top: calc(var(--scale-factor)*294.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.06729);" role="presentation">limit<span dir="ltr" style="left: calc(var(--scale-factor)*414.43px); top: calc(var(--scale-factor)*294.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.868293);" role="presentation">ed to wage increases to <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*315.19px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the<span dir="ltr" style="left: calc(var(--scale-factor)*85.58px); top: calc(var(--scale-factor)*315.19px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.10285);" role="presentation">ir <span dir="ltr" style="left: calc(var(--scale-factor)*95.42px); top: calc(var(--scale-factor)*315.19px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.890018);" role="presentation">demand for an eight-<span dir="ltr" style="left: calc(var(--scale-factor)*194.45px); top: calc(var(--scale-factor)*315.19px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.903433);" role="presentation">hour working day in the rice fields, these women <span dir="ltr" style="left: calc(var(--scale-factor)*428.59px); top: calc(var(--scale-factor)*315.19px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.853288);" role="presentation">engaged <span dir="ltr" style="left: calc(var(--scale-factor)*471.10px); top: calc(var(--scale-factor)*315.19px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.878247);" role="presentation">themselves <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*335.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.953541);" role="presentation">in local and national political life, learning to <span dir="ltr" style="left: calc(var(--scale-factor)*294.65px); top: calc(var(--scale-factor)*335.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.933111);" role="presentation">to turn the <span dir="ltr" style="left: calc(var(--scale-factor)*348.67px); top: calc(var(--scale-factor)*335.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.937162);" role="presentation">confining rules and laws of the very <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*356.59px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.895336);" role="presentation">legislation that enchained them into <span dir="ltr" style="left: calc(var(--scale-factor)*241.73px); top: calc(var(--scale-factor)*356.59px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.891599);" role="presentation">weapons to claim new rights<span dir="ltr" style="left: calc(var(--scale-factor)*376.15px); top: calc(var(--scale-factor)*356.59px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.910063);" role="presentation">. Their fight and their <span dir="ltr" style="left: calc(var(--scale-factor)*478.54px); top: calc(var(--scale-factor)*356.59px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.820568);" role="presentation">successes <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*377.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.842215);" role="presentation">are <span dir="ltr" style="left: calc(var(--scale-factor)*88.46px); top: calc(var(--scale-factor)*377.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.900596);" role="presentation">celebrated in various r<span dir="ltr" style="left: calc(var(--scale-factor)*195.17px); top: calc(var(--scale-factor)*377.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.918617);" role="presentation">ice field songs, the texts of which allow us to reflect <span dir="ltr" style="left: calc(var(--scale-factor)*447.46px); top: calc(var(--scale-factor)*377.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.882244);" role="presentation">on the existence <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*397.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.937389);" role="presentation">of a symbiotic link <span dir="ltr" style="left: calc(var(--scale-factor)*162.26px); top: calc(var(--scale-factor)*397.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.878501);" role="presentation">between <span dir="ltr" style="left: calc(var(--scale-factor)*207.17px); top: calc(var(--scale-factor)*397.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.877584);" role="presentation">the socialist party and these <span dir="ltr" style="left: calc(var(--scale-factor)*340.15px); top: calc(var(--scale-factor)*397.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.916157);" role="presentation">heroic <span dir="ltr" style="left: calc(var(--scale-factor)*372.55px); top: calc(var(--scale-factor)*397.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912099);" role="presentation">women<span dir="ltr" style="left: calc(var(--scale-factor)*407.83px); top: calc(var(--scale-factor)*397.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.893687);" role="presentation">, who took on the double <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*418.77px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.913972);" role="presentation">role of teaching <span dir="ltr" style="left: calc(var(--scale-factor)*151.70px); top: calc(var(--scale-factor)*418.77px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.905684);" role="presentation">socialism to other workers and <span dir="ltr" style="left: calc(var(--scale-factor)*301.37px); top: calc(var(--scale-factor)*418.77px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912551);" role="presentation">exercising <span dir="ltr" style="left: calc(var(--scale-factor)*353.59px); top: calc(var(--scale-factor)*418.77px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.911239);" role="presentation">authority over the governing bodies <span dir="ltr" style="left: calc(var(--scale-factor)*70.94px); top: calc(var(--scale-factor)*439.41px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.916803);" role="presentation">of the new party.